Red deer gender and populations analysis using scats’ volatile profile - Oliveira, Maria João Saraiva de (2014)
Current populations of red deer (Cervus elaphus) in Portugal derive from recent reintroduction processes and natural dispersion movements from Spain. These movements promote the expansion of the species and reproduction among different populations, increasing the need for more sophisticated methodologies able to differentiate populations and determine sex-ratio, two demographic parameters used in the management of populations. Headspace solid phase microextraction and comprehensive two-dimensional chromatography coupled to mass spectrometry for time of flight gas phase mode (HS-SPME/GC×GC– ToFMS) arises as a possible solution to the determination of these parameters. Thus, this work aims to test for differences between red deer populations, using scats from natural fenced red deer populations as a model to distinguish between sexes. The obtained volatiles are an attempt to determine specific sets of compounds or chemical families’ markers for males, females and for each population, targeting the use in wildlife approaches. In fact, results showed that populations and gender successful differentiation was based on a sub-set of probably, diet and chemical communication compounds, respectively. The mechanism underling this differentiation is probably the interaction of genetics and environment leading to changes in animals’ physiology, based in the expressed volatile metabolites detected in the scats. The absence of literature data that relates the tentatively identified compounds (mainly aliphatic ketones and hydrocarbons) to chemical signals between red deer requires future bioassays testing the achieved compounds to predetermined behaviours. It is considered that the results and conclusions of this work may be applied to big scale wild populations, allowing the assessment of ecological parameters that otherwise would be expansive and time consuming.